Problem-Based Learning in Outdoor Study Settings Affects Learning Motivation and Science Learning Outcomes - Sulasmini, Ni Made; Ida Bagus Putu Arnyana; I Made Candiasa (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Student learning motivation could be more optimal, and learning outcomes could be higher. Innovation in the learning process is needed to increase student motivation and learning outcomes. This study aims to determine the difference in learning motivation and science results with problem-based learning in outdoor study settings and conventional learning models of grade IV elementary school students. This type of research is a quasi-experiment with a posttest-only control group design. The population of this study was all grade IV elementary school students, consisting of 80 students. A total of 65 students were selected as samples determined by random sampling. Data collection using non-test methods in the form of learning motivation questionnaires and multiple-choice objective test methods to measure student science learning outcomes. Data analysis using MANOVA analysis assisted by IBM SPSS Statistic 26.00 for Windows. The results showed differences in learning motivation and science learning outcomes simultaneously between students who followed model learning with problem-based learning in outdoor study settings and conventional learning. There are differences in the learning motivation of students who follow the learning model with problem-based learning in outdoor study settings with conventional learning. There are differences in science learning outcomes between students who follow model learning and problem-based learning in outdoor study settings and those who follow conventional learning. So, problem-based learning in outdoor study settings influences learning motivation and science learning outcomes of grade IV elementary school students.